EVALUATION OF POLLEN VIABILITY UNDER IN VITRO CONDITIONS IN TUBEROSE (POLIANTHES TUBEROSA) - P. RANCHANA; M. KANNAN; M. JAWAHARLAL (The Bioscan, 2015)
An experiment on pollen studies in tuberose under in vitro conditions was conducted in the Department of Floriculture and Landscaping, Tamil Nadu Agricultural Univeristy, Coimbatore during the year 2012- 13. The ten single genotypes viz.,Calcutta Single, Hyderabad Single, Kahikuchi Single, Mexican Single, Navsari Local, Phule Rajani, Prajwal, Pune Single, Shringar and Variegated Single were used for this study. Variegated Single showed its superiority in pollen viability (96.73%) and germination (98.61%) than other genotypes and it is followed by Phule Rajani (90.52% and 90.96%) under in vitro.High level of pollen germination was observed when PhuleRajani was crossed with Hyderabad Single (75%), Kahikuchi Single (80%), Mexican Single (94%) and Variegated Single (94%). Likewise, high level of pollen grain was noticed when Variegated Single was crossed with Calcutta Single (75%), Kahikuchi Single (57%), Mexican Single (81%), Navsari Local (50%) and Pune Single (75%) under in vitro. Hence, the success of hybridization by using the genotypes Variegated Single and Phule Rajani as a female parent will be highly helpful to develop new hybrids.